Nodular lymphocyte predominant Hodgkin lymphoma: executive summary of the American radium society appropriate use criteria. Issue 5 (16th April 2021) - Ballas, Leslie K.; Metzger, Monika L.; Milgrom, Sarah A.; Advani, Ranjana; Bakst, Richard L.; Dabaja, Bouthaina S.; Flowers, Christopher R.; Ha, Chul S.; Hoppe, Bradford S.; Mansur, David B.; Pinnix, Chelsea C.; Plastaras, John P.; et al.
Abstract: This guideline for nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) by the American Radium Society was developed by a multidisciplinary expert panel of medical, pediatric, and radiation oncologists convened to formulate guidelines for evaluation and treatment. The guideline development was based on an in-depth literature review and the application of a well-established consensus methodology (modified Delphi) to rate the appropriateness of the recommendations by the panel. Given the scarcity of compelling data for strong recommendations for a rare lymphoma that has been shown to be more indolent than classical Hodgkin lymphoma, in instances where evidence is not available or equivocal, expert opinion guided the recommendations. Four clinical variants exemplify common scenarios and represent the consensus recommendations for patients with nodular lymphocyte Hodgkin lymphoma. A summary of the available published literature is also presented.